17. CLINICAL CHARACTERISTICS AND RESULTS OF TREATMENT OF HAND FOOT MOUTH DISEASE IN CHILDREN AT NGHE AN OBSTETRICS AND PEDIATRICS HOSPITAL IN 2020-2022 (Vietnam Journal of Community Medicine, 2024)
Objective: The study aimed to evaluate the clinical characteristics and treatment results of hand, foot and mouth disease.Subjects and methods: Retrospective, prospective, cross-sectional study of 450 children treated at Nghe An Obstetrics and Pediatrics Hospital.Results: The disease occurred in both sexes, in which males accounted for more than females with male/female ratio is 1.8/1. The highest age group affected, from 36 months to under 60 months of age, accounted for 48.9%. The majority of children have clinical grade 2a (85.1%). Children 100% develop a rash on the palms and soles. Patients with skin and mucosal lesions in the form of blisters accounted for 40.9%; erythema accounted for 34.4%. The drugs used to treat hand, foot and mouth disease mainly reduce fever (87.7%) and sedative (88.2%). Only 1.8% of children were assigned Immunoglobulin IV. 100% of children were cured of the disease and no children had sequelae.Conclusion: Most of the children had grade 2a and were completely cured.
Keywords: Hand, foot and mouth disease, children, Nghe An Obstetrics and Pediatrics Hospital.